Integrated Metabolomics and Transcriptomic Analysis of Hepatopancreas in Different Living Status Macrobrachium nipponense in Response to Hypoxia - Lei Xu; Wenyi Zhang; Hui Qiao; Sufei Jiang; Yiwei Xiong; Shubo Jin; Yongsheng Gong; Hongtuo Fu (MDPI AG, 2021)
As the basic element of aerobic animal life, oxygen participates in most physiological activities of animals. Hypoxia stress is often the subject of aquatic animal research. Macrobrachium nipponense, an economically important aquatic animal in southern China, has been affected by hypoxia for many years and this has resulted in a large amount of economic loss due to its sensitivity to hypoxia; Metabolism and transcriptome data were combined in the analysis of the hepatopancreas of M. nipponense in different physiological states under hypoxia; A total of 108, 86, and 48 differentially expressed metabolites (DEMs) were found in three different comparisons (survived, moribund, and dead shrimps), respectively. Thirty-two common DEMs were found by comparing the different physiological states of M. nipponense with the control group in response to hypoxia. Twelve hypoxia-related genes were identified by screening and analyzing common DEMs. GTP phosphoenolpyruvate carboxykinase (PEPCK) was the only differentially expressed gene that ranked highly in transcriptome analysis combined with metabolome analysis. PEPCK ranked highly both in transcriptome analysis and in combination with metabolism analysis; therefore, it was considered to have an important role in hypoxic response. This manuscript fills the one-sidedness of the gap in hypoxia transcriptome analysis and reversely deduces several new genes related to hypoxia from metabolites. This study contributes to the clarification of the molecular process associated with M. nipponense under hypoxic stress.